Therapeutic Applications of Functional Nanomaterials for Prostatitis - Chun-Ping Liu; Chun-Ping Liu; Zi-De Chen; Zi-Yan Ye; Dong-Yue He; Yue Dang; Zhe-Wei Li; Lei Wang; Miao Ren; Zhi-Jin Fan; Hong-Xing Liu (Frontiers Media S.A., 2021)
Prostatitis is a common disease in adult males, with characteristics of a poor treatment response and easy recurrence, which seriously affects the patient's quality of life. The prostate is located deep in the pelvic cavity, and thus a traditional infusion or other treatment methods are unable to easily act directly on the prostate, leading to poor therapeutic effects. Therefore, the development of new diagnostic and treatment strategies has become a research hotspot in the field of prostatitis treatment. In recent years, nanomaterials have been widely used in the diagnosis and treatment of various infectious diseases. Nanotechnology is a promising tool for 1) the accurate diagnosis of diseases; 2) improving the targeting of drug delivery systems; 3) intelligent, controlled drug release; and 4) multimode collaborative treatment, which is expected to be applied in the diagnosis and treatment of prostatitis. Nanotechnology is attracting attention in the diagnosis, prevention and treatment of prostatitis. However, as a new research area, systematic reviews on the application of nanomaterials in the diagnosis and treatment of prostatitis are still lacking. In this mini-review, we will highlight the treatment approaches for and challenges associated with prostatitis and describe the advantages of functional nanoparticles in improving treatment effectiveness and overcoming side effects.